Atypical Fibroxanthoma Arising in a Scar of Discoid Lupus Erythematosus. Issue 5 (September 2014) - De Francesco, Vincenzo; Errichetti, Enzo; Pegolo, Enrico; Stinco, Giuseppe
Background: Malignant change in the scars of discoid lupus erythematosus (DLE) is a well-known event. In most cases, tumors are of epithelial origin, particularly squamous cell carcinomas and, less frequently, basal cell carcinomas and keratoacanthomas. The onset of soft tissue sarcomas in a DLE scar is a very rare event, however, because only one case of malignant fibrous histiocytoma has been described in the literature. Objective: We describe the first documented report of atypical fibroxanthoma (AFX) arising in an old scar of DLE. Results: Although we cannot exclude an accidental association between AFX and DLE, our case emphasizes that patients with DLE may develop AFX in the context of an old scar. Conclusion: Our finding further underlines the importance of strict and long-term surveillance of people with DLE to identify and remove eventual tumors at an early stage.